2021
DOI: 10.3390/en14123527
|View full text |Cite
|
Sign up to set email alerts
|

Using Value Stream Mapping to Eliminate Waste: A Case Study of a Steel Pipe Manufacturer

Abstract: Value Stream Mapping (VSM) is a popular and easy tool for visualizing production processes in enterprise. It allows one to eliminate or reduce waste, i.e., activities that do not create added value for the customer. The versatility of this tool allows it to be used in industry. There are theoretical, methodological, and practical aspects encountered by practitioners in developing Value Stream Mapping (VSM) for a specific manufacturing industry, but they are not fully resolved and require clarification. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…A simulation model was run to investigate the basic performance measures, as well as assessing the system settings. Salwin et al (2021) explained the application of VSM in the manufacture of steel pipes. Their purpose was to present the VSM method as part of the analysis and process improvement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A simulation model was run to investigate the basic performance measures, as well as assessing the system settings. Salwin et al (2021) explained the application of VSM in the manufacture of steel pipes. Their purpose was to present the VSM method as part of the analysis and process improvement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In his case study, Salwin et al (2021) found that the VSM is like a snapshot of the production status at the moment, which means that the day taken into account for the mapping may have run perfectly, but the next day may present different problems, so that the next VSM may vary significantly. It is perhaps true that the theory is far from the practice and application of Lean tools [15].…”
Section: Specific Observationsmentioning
confidence: 99%
“…We have witnessed a strong emphasis on environmental protection, Industry 4.0 and digital solutions (Abou-foul et al, 2020;Tronyoll et al, 2020;Gaiardelli et al, 2021). Both manufacturing and service companies focus their efforts to satisfy an ever-higher number of needs of individual and institutional clients (Salwin et al, 2021a;Salwin et al, 2021b;Lipak and Salwin, 2019). This gives rise to the need to generate and develop various types of inno-vations (Kukurba et al, 2021;Salwin et al, 2021a;Boons et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Both manufacturing and service companies focus their efforts to satisfy an ever-higher number of needs of individual and institutional clients (Salwin et al, 2021a;Salwin et al, 2021b;Lipak and Salwin, 2019). This gives rise to the need to generate and develop various types of inno-vations (Kukurba et al, 2021;Salwin et al, 2021a;Boons et al, 2013). More often than not, innovations are created by start-ups, that is young innovative enterprises or temporary organisations searching for a business model that will guarantee them additional values.…”
Section: Introductionmentioning
confidence: 99%